Significance of the pulsatility index in the evaluation of hemodynamic changes in peripheral arterial circulation in the obese treated with orlistat - Hajduković, Zoran; Dragović, Tamara; Radjen, Slavica; Marinković, Dejan M.; Ratković, Nenad; Kiković, Saša (Vojnosanitetski pregled, 2021)
Background/Aim. Prolonged hyperinsulinemia accelerates the process of endothelial dysfunction and arteriosclerotic changes affecting the development of cardiovascular and cerebrovascular diseases. There are various measuring techniques for the evaluation of early functional changes in the arterial wall such are flow-mediated endothelium-dependent vasodilation, impulse wave analysis, intima-media thickness assessment, venous plethysmography and so on, however, each having certain limitations in results interpretation. The aim of this study was to indicate the correlation of pulsatility index that shows peripheral arterial contractility with the changes in metabolic parameters under the conditions of insulin resistance. Method. The study included a total of 35 healthy obese subjects with the values of body mass index more than 30 kg/m2 randomized with double blind design into two groups: placebo and orlistat. The extent of insulin sensitivity was calculated on the basis of the values of glycemia and insulinemia using the formula (?). Results. The obtained results suggest a statistically significant improvement in the pulsatility index in the group orlistat (p < 0.002), while there was no such improvement in the placebo group. Conclusion. The results obtained in this study indicate the improvement in insulin sensitivity within early arteriosclerosis as a significantly favorable factor for peripheral arterial circulation additionally supported by the reduction in the level of lipid fractions, especially triglycerides. Early hemodynamic changes under the conditions of the reduced insulin resistance are characterized by the increase in arterial wall contractility evaluated with pulsatility index determination.